2023
DOI: 10.1111/mec.16924
|View full text |Cite
|
Sign up to set email alerts
|

Genetic fine‐mapping reveals single nucleotide polymorphism mutations in the MC1R regulatory region associated with duck melanism

Abstract: Birds are among the most colourful terrestrial vertebrates, with various plumage colours and patterns. We conducted a genome‐wide association study (GWAS) on an intercross F2 population of Pekin ducks and mallards (n = 722) and identified a 1.57‐Mb genetic region (Chr11: 20,176,480–21,750,101 bp) related to duck melanism. Fine mapping by linkage disequilibrium (LD) and FST analysis narrowed the final candidate region to a region of 22,500 bp (Chr11: 20,677,500–20,700,000 bp) including three coding genes, TCF25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…It activates the TYR core enhancer, which helps to regulate the tyrosinase gene in melanocytes ( Yun et al, 2019 ). At present, the predominant candidate genes related to duck feather color are TYR ( Sultana et al, 2018 ), TYRP1 ( Xi et al, 2020 ), DCT ( Sultana et al, 2018 ), MC1R ( Liu et al, 2023a ), EDNRB2 ( Guo et al, 2022 ), and MITF ( Zhou et al, 2018 ; Lin et al, 2019 ; Wang et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It activates the TYR core enhancer, which helps to regulate the tyrosinase gene in melanocytes ( Yun et al, 2019 ). At present, the predominant candidate genes related to duck feather color are TYR ( Sultana et al, 2018 ), TYRP1 ( Xi et al, 2020 ), DCT ( Sultana et al, 2018 ), MC1R ( Liu et al, 2023a ), EDNRB2 ( Guo et al, 2022 ), and MITF ( Zhou et al, 2018 ; Lin et al, 2019 ; Wang et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…For these products, white feather ducks are favored by consumers. The variations of feather color in birds are related to the distribution, content and proportion of pigments ( Liu et al, 2023a ). Melanin is the main pigment, which mainly affects the color of feathers and the depth of skin color.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in humans, an SNP in the promoter of the SLC45A2 gene has been linked to variations in skin color (Graf et al, 2007). In ducks, the black plumage phenotype is determined by a mutation within the regulatory region of the MC1R gene (Liu et al, 2023). Similarly, studies on different chicken breeds have revealed that mutations in the promoter regions of genes like MITF , TYR , ASIP, and GJA5 play a role in influencing skin color (Li et al, 2021; Wang et al, 2018; Yu et al, 2019, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Though the pleiotropic nature of the POMC gene has been posited to explain associations between melanin‐based pigmentation and other phenotypic traits, that is, melanin‐associated phenotypes, molecular evidence is largely absent (McNamara et al., 2021; San‐Jose & Roulin, 2018). What has been well described is structural genetic variation at MC1R and respective regulatory regions affecting melanin‐based pigmentation in several bird species including domestic breeds (Kerje et al., 2003; Liu et al., 2023; Mundy, 2005). However, a lack of associations has also been reported particularly after correcting for the effect of population structure (Avilés et al., 2019; Hoffman et al., 2014; MacDougall‐Shackleton et al., 2003).…”
Section: Introductionmentioning
confidence: 99%